Enhancing Imagination Through Finger Painting Activities in 5-6 Year Olds - Rohali, Alia; Sitorus, Masganti (Journal of Islamic Education Students (JIES), 2025)
The development of imagination in early childhood is crucial for supporting creativity and cognitive abilities. This study aims to enhance the imagination of children aged 5-6 years through the finger painting activities┬áusing Classroom Action Research (CAR) with two cycles, involving 15 children aged 4-6 years as subjects. Initial observations revealed that most children were in the "not yet developed" category. In Cycle I, free experimentation with finger painting improved their status to "starting to develop" and "developing as expected." In Cycle II, structured instructions and more varied colors resulted in most children reaching the "developing as expected" category. Finger painting proved effective in fostering imagination, creativity, and confidence in early childhood.┬á┬á┬á